Adsorption Behavior of MWAR Toward Gd(III) in Aqueous Solution - Chunhua Xiong; Caiping Yao (Iranian Journal of Chemistry & Chemical Engineering, 2010)
Adsorption and desorption behavior of Gd(III) ionon macroporous weak acid resin (MWAR) had been investigated.The influence of operational conditions such as contact time, initial concentration of Gd(III) ion, initial pH of solution and temperature on the adsorption of Gd(III) ion had been examined. Experimental data were exploited for kinetic and thermodynamic evaluations related to the adsorption processes. Adsorption isotherms were attempted to be obtained the model parameters at different temperature and to be fitted better to Langmuir model than to Freundlich model within the studied concentration range. The maximum adsorption capacity of Gd(III) ion on MWAR was 384 mg/gat 298 K, calculated from Langmuir model. The apparent activation energy was Ea = 18.0 kJ/mol and adsorption rate constant was k298 = 1.22×10-5 s-1, respectively. Thermodynamic parameters such as changes in the enthalpy (ΔH), entropy (ΔS) and Gibb’s free energy (ΔG) indicated that Gd(III) ion adsorption by MWAR was an endothermic and spontaneous process in nature, and more favorable adsorption was obversed when the ambient temperature was high Gd(III) can be eluted with the composition of 0.5mol/L HCl and 0.5 mol/L NaCl solution.